Material and wave relaxation phenomena effects on the rheology of Maxwell nanofluids - Ahmed, Awais; Alhowaity, Sawsan; Ghoneim, Mohamed E.; Gamaoun, Fehmi; Tag-eldin, Elsayed; Yassen, Mansour F.; Sarfraz, Mahnoor (Frontiers in Physics, 2022)
This manuscript analyzes the thermal and mass transport in magnetohydrodynamic (MHD) Maxwell nanofluid over a cylinder stretched along the z-direction. Besides, the Cattaneo-Christov diffusion theory and Buongiorno's model are employed to model the problem. The influence of Joule heating, chemical reaction rate, and heat generation is also taken into account. Appropriate similar variables are utilized to transform the constitutive equations. A semi-analytical method, namely the homotopy analysis method (HAM) in Wolfram Mathematica, is employed to compute the problem's solution. It is deduced that the flow behavior varies inversely by augmenting the values Maxwell parameter; however, the thermal and solutal transport displays the opposite trend. Additionally, the flow field endures resistance due to the presence of the magnetic field; but Joule heating enhanced the energy and mass transport phenomena. The results procured for the coefficient of skin friction along the radial direction are in remarkable agreement with the ones in the literature.